2002
DOI: 10.1086/338492
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Evolution of the X‐Ray Remnant of SN 1987A

Abstract: We report on the results of our monitoring program of the remnant of SN 1987A with the Advanced CCD Imaging Spectrometer (ACIS) on board the Chandra X-ray Observatory. Two new observations have been performed in AO2, bringing the total to four monitoring observations over the past two years. Over this time period, new techniques for correction of "Charge Transfer Inefficiency (CTI)" and for use of charge spreading to provide angular resolution somewhat better than the pixel size of the CCD detector have become… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
127
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(140 citation statements)
references
References 36 publications
10
127
3
Order By: Relevance
“…Subsequently, Hasinger et al (1996) tracked a steady increase of the soft X-ray flux over 4 yr with ROSAT. Extensive work has since been done by the Chandra Park et al 2002Park et al , 2004Park et al , 2005Park et al [hereafter P05], 2006Park et al , 2007Zhekov et al 2005Zhekov et al , 2006) and XMM-Newton groups (Haberl et al 2006, hereafter H06;Aschenbach 2007, hereafter A07). The general picture gleaned from these studies is of a bimodal plasma distribution present in the region between the forward and reverse shocks (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Hasinger et al (1996) tracked a steady increase of the soft X-ray flux over 4 yr with ROSAT. Extensive work has since been done by the Chandra Park et al 2002Park et al , 2004Park et al , 2005Park et al [hereafter P05], 2006Park et al , 2007Zhekov et al 2005Zhekov et al , 2006) and XMM-Newton groups (Haberl et al 2006, hereafter H06;Aschenbach 2007, hereafter A07). The general picture gleaned from these studies is of a bimodal plasma distribution present in the region between the forward and reverse shocks (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing a Monte Carlo simulation (Burrows et al, 2000;Park et al, 2002), we estimate a 90% upper limit on the 3−8 keV band point source counts based on the latest ACIS image of SNR 1987A. We assume a power law spectrum of a photon index Γ = 1.7 for the putative neutron star in order to estimate the X-ray flux corresponding to the Hasinger, Aschenbach, & Trümper (1996).…”
Section: Point Sourcementioning
confidence: 99%
“…Considering its core-collapse, Type II SN origin from a massive progenitor (Sonneborn, Altner, & Kirshner, 1987), as confirmed by the detection of the accompanying neutrino burst (Koshiba et al, 1987), the presence of a compact stellar remnant is predicted for SNR 1987A. There has, however, been no evidence for a pointlike source at the center of the remnant, which has been attributed to optically thick stellar ejecta material surrounding the putative central point source (Burrows et al, 2000;Park et al, 2002Park et al, , 2004. As the blast wave eventually sweeps through the main body of the dense in-ner ring, a dramatic increase of the X-ray flux and morphological/spectral changes of SNR 1987A are expected.…”
Section: Introductionmentioning
confidence: 98%
“…Shtykovskiy et al (2005) obtained a luminosity limit in the 2-10 keV band of 5 × 10 34 erg s −1 using the XMM-Newton. Park et al (2002Park et al ( , 2004 obtained upper limits of 5.5×10 33 erg s −1 and 1.5 × 10 34 erg s −1 in the same X-ray band using Chandra.…”
Section: Introductionmentioning
confidence: 94%
“…Yu & Xu (2011) found that the thermal X-ray luminosity has a similar relation with thatĖ, L ∞ bol ∼ 10 −3Ė . Since the observations have given a upper limit of thermal X-ray luminosity L ∞ bol ∼ 10 34 erg s −1 (Park et al 2002(Park et al , 2004, we can get an upper limit of spin energy loss rateĖ. And we can further make a constraint to the parameters of spin and magnetic field of the possible pulsar, becauseĖ is the function of spin and magnetic field,…”
Section: Constraints On the Parameters Via Heating Processesmentioning
confidence: 99%